The utilisation of di/tri peptides by Stagonospora nodorum is dispensable for wheat infection - Solomon, P.; Thomas, S.; Spanu, P.; Oliver, Richard (2004)
A gene required for di/tripeptide transport in the necrotrophic wheat pathogen Stagonospora nodorum has been cloned, characterised and inactivated by homologous recombination. Recent genome sequencing projects have revealed the presence of fungal homologues though Ptr2 is the first di/tripeptide transporter to be cloned and function characterised from a fungus. Analysis of Ptr2 expression in vitro revealed strong expression in the absence of nitrogen and in the presence of carbon; interestingly there was very low expression in the absence of both nitrogen and carbon. The expression of Ptr2 during infection showed the gene was significantly up-regulated during the initial stages of infection before decreasing to a lower constitutive level suggesting the fungus may be nitrogen starved during the pre-penetration stage of the infection. Ptr2 was inactivated by homologous gene recombination resulting in the strain S. nodorum ptr2. Peptide uptake studies of S. nodorum ptr2 suggest that Ptr2 is solely responsible for the uptake of di/tripeptides. The ability of S. nodorum ptr2 to cause infection was also examined. Pathogenicity assays revealed that the mutant strain was fully pathogenic. As the gene has been shown to be fully responsible for di/tripeptide transport, this implies that the uptake of these small peptides is not required for S. nodorum pathogenicity on wheat leaves.